2011
DOI: 10.1152/ajpregu.00121.2011
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-directed myostatin inhibition enhances muscle mass and function in tumor-bearing mice

Abstract: Cancer cachexia describes the progressive skeletal muscle wasting and weakness in many cancer patients and accounts for >20% of cancer-related deaths. We tested the hypothesis that antibody-directed myostatin inhibition would attenuate the atrophy and loss of function in muscles of tumor-bearing mice. Twelve-week-old C57BL/6 mice received a subcutaneous injection of saline (control) or Lewis lung carcinoma (LLC) tumor cells. One week later, mice received either once weekly injections of saline (control, n = 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
95
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 98 publications
(101 citation statements)
references
References 47 publications
3
95
1
2
Order By: Relevance
“…This is important as the loss of muscle strength in cancer cachexia patients is known to significantly contribute not only to the morbidity and mortality of the condition, but also to the quality of life for these patients (28). Our data are also consistent with results from a recent study in which a myostatin antibody was shown to prevent the loss of muscle mass and strength in a Lewis Lung carcinoma tumor model (16).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is important as the loss of muscle strength in cancer cachexia patients is known to significantly contribute not only to the morbidity and mortality of the condition, but also to the quality of life for these patients (28). Our data are also consistent with results from a recent study in which a myostatin antibody was shown to prevent the loss of muscle mass and strength in a Lewis Lung carcinoma tumor model (16).…”
Section: Discussionsupporting
confidence: 90%
“…In addition, antisense RNA administration has resulted in less skeletal muscle loss in a preclinical model of cancer cachexia (12). Although antibody-mediated myostatin inhibition has been shown to reduce skeletal muscle loss in several noncancer preclinical models of muscle wasting (13)(14)(15), only one previous report describes inhibition in a model of cancer cachexia (16). We report here the preclinical characterization of LSN2478185, a myostatin neutralizing mouse IgG1 monoclonal antibody and its derivative LY2495655, a humanized neutralizing monoclonal antibody to myostatin that can significantly attenuate loss of skeletal muscle mass and function associated with tumor burden.…”
Section: Introductionmentioning
confidence: 99%
“…TA muscles were mounted in an embedding medium and frozen in thawing isopentane for later histochemical and biochemical analyses. The TA muscle was chosen because 1) it is of sufficient mass and cross-sectional area (CSA) for conducting these analyses, 2) we have found that it is susceptible to atrophy and functional impairment in the C-26 (24) and LLC tumor-bearing models (23), and 3) we have previously investigated histochemical and biochemical properties of this muscle in the C-26 (24) and LLC tumor-bearing models (23). Although it would be of interest to also examine histochemical and biochemical properties in muscles predominantly composed of type I fibers, such as in the soleus muscle, the small mass of the soleus (5-6 mg) precludes its use in these analyses.…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that eicosanoids also mediate inflammation in cancer cachexia [38][39][40] . There is considerable evidence that signaling through cytokines and myostatin/activin pathways has a role in cancer cachexia and anorexia [41][42][43] ( Figure 1). Numerous cytokines, including tumor necrosis factor-alpha (TNF-α), interleukin-1 (IL-1), IL-6, and interferon-gamma (IFN-γ), have been postulated to play a role in the etiology of cancer cachexia [44][45][46][47][48][49][50][51][52] .…”
Section: Inflammationmentioning
confidence: 99%